Daily almond consumption in cardiovascular disease prevention via LDL-C change in the U.S. population: a cost-effectiveness analysis. - Wang, Jifan.; Lee Bravatti, Michelle A.; Johnson, Elizabeth J.; Raman, Gowri. (Tufts University. Tisch Library., 2020)
Keywords: Almond, Cost-effectiveness analysis, Cardiovascular disease, Heart disease, Stroke, Myocardial infarction.; Springer Open.